SKRINING BEBERAPA JAMUR ENDOFIT TUMBUHAN DARI PULAU ENGGANO, BENGKULU SEBAGAI ANTIBAKTERI DAN ANTIOKSIDAN - Dewi Wulansari; Aldho Pramana Putra; Muhammad Ilyas; Praptiwi Praptiwi; Ahmad Fathoni; Kartika Dyah Palupi; Andria Agusta (Research Center for Biology-Indonesian Institute of Sciences, 2016)
Fungal endophytes have been known as sources for bioactives with high chemical structure variability. This study aimed to screen extracts of some endophytic fungi associated with plants from Enggano Island as antioxidant and antibacterial using thin layer chromatography (TLC) bioautography method. Antibacterial ativity was performed against Escherichia coli and Staphylococcus aureus. Seventeen out of 22 extracts showed growth inhibition activity against both bacteria, while 16 extracts were active as DPPH free radical scavenging agents. Further determination on IC50 value of four prominent extracts revealed that fungal endophytes AK3018-1, FC-1, KC-4, and SO-3 have IC50 value of 85, 84, 704, and 347 ?g/ml, respectively in DPPH radical scavenging method. Extracts of fungal endophytes CR-3, CS-2, and SM-2 showed prominent antibacterial activity among other extracts, indicated by wide clear white zone around the spot. Further evaluation on minimum inhibitory concentration (MIC) of those three extracts by microdilution method showed that CR-3, CS-2, and SM-2 have MICs value of 512, >512, and 64µg/ml, respectively against S. aureus.Fungal endophytes AK3018-1, FC-1, KC-4, SO-3, CR-3, CS-2, and SM-2 were respectively isolated from Dioscorea bulbifera tuber, Fibraurea chloroleuca twig, Knema cinerea twig, Smilax odoratissima stem, Cryptocarya sp. twig, Calophyllum soulattri twig, and Smilaxmacrophylla stem.